Network and Business Performance Installed in Coworking Spaces: Evidence and Associations - Hérique Costa Ribeiro de Lima; Rodolfo Araujo de Moraes Filho; Brigitte Renata Bezerra de Oliveira; Telma Lúcia de Andrade Lima; Marcos Felipe Falcão Sobral (Administrative Sciences)
Space sharing for companies has become a trend in the last decade. Many of the benefits of these spaces go beyond the financial scope, creating real value-added processes from these spaces. This study examines the associations between networks developed in coworking spaces and business performance. This research was quantitative, exploratory, and descriptive ex post facto. A survey was conducted among companies installed in coworking spaces in Recife, Brazil. The sample consisted of 77 valid respondents, and the data were analyzed using descriptive and inferential statistics that measure central tendency, factor analysis, and Spearman (ordinal indicators) and Pearson (resulting factors) correlations, in addition to reliability tests and adequacy of the sample, necessary in the refinement of the scales. This study makes a theoretical contribution by specifying the concept of coworking, a topic still underexplored in the literature, and by defining networks in this context, which allowed for the development of a measurement scale. It also discusses the performance construct and its measurement classes, which showed significant internal consistency. Despite the consistency in the data, only the hypothesis of a positive and significant association between network and market performance was partially accepted, demonstrating that more than the network alone was needed to generate results among coworkers. This lack of association contradicts the literature as it is the most discussed aspect in qualitative studies on coworking and suggests that the network may not be a final resource but rather a means by which users obtain benefits such as benchmarks, creative ideas, and adaptation of business practices.